Kontribusi Tingkat Sosial Ekonomi Orang Tua, Motivasi, dan Fasilitas Belajar Terhadap Hasil Belajar Matematika pada Siswa Kelas VIII di SMP Negeri 2 Colomadu - Puspitasari, Yuni, Prof. Dr. Sutama, M.Pd (2017)
This study has four purpose, is to examine : 1) the contribution of parental socio economic level, motivation, and learning facilities to the methematics learning outcome. 2) the contribution of parental socio economic level to mathematics learning outcome. 3) the contribution of learning motivation to mathematics learning outcome. 4) the contribution of learning facilities to mathematics learning outcome. This study is qualitative research. The population of this study is all of 8th grade students in SMP Negeri 2 Colomadu. These are taken as sample 161 students by proporsional random sampling. Tecnique of collecting data uses documentation and questionnaire, technique of analyzing data uses dauble regresion analysis and had previously been classical assumption test. The result of study: 1) the parental socio economic level, motivation, and learning facilities simultaneously have contribution on mathematics learning outcome of 8th grade in SMP N 2 Colomadu by ∝=5%. Thet independent variabel gives contribution 85,5%. 2) the parental socio economic level gives positive contribution on mathematics learning outcome by ∝=5%. 3) learning motivation gives positve contribution on mathematics learning outcome by ∝=5%. 4) learning facilities give positive contribution on mathematics learning outcome by ∝=5%.